Covid-19 and Moral Degeneration Among the Juveniles: A Case Study of Nyanga Church of Uganda in Kyakabunga Archdeaconry, North Ankole Diocese - Patrick Natwijuka (Uganda Christian University, 2025)
The purpose of this study was to investigate the impact of COVID-19 on moral degeneration among juveniles in Nyanga Church of Uganda, Kyakabunga Archdeaconry, North Ankole Diocese. The study was guided by three objectives; to examine the impact of COVID-19 on moral values among juveniles in Nyanga Church of Uganda, to identify the factors contributing to moral degeneration among juveniles during the COVID-19 pandemic and to explore the coping mechanisms employed by juveniles to maintain moral values during the pandemic. This study employed a qualitative method research design. The study included descriptive research where both primary and secondary data were collected. The sample size of the study was 120 respondents. The study concluded that the COVID-19 pandemic significantly disrupted the traditional moral support systems for juveniles, particularly schools and churches, leading to increased vulnerability to immoral behavior. The style of parenting, degree of community engagement, and availability of spiritual and social guidance during this period played a critical role in either aggravating or mitigating moral degeneration. Based on the findings, the following recommendations were made; Parents should be encouraged through church programs and community forums to adopt authoritative parenting, which balances discipline with warmth, communication, and guidance and Churches should encourage families to maintain regular home-based devotions and spiritual instruction. Even in times of public restrictions, churches should distribute devotional materials, create family prayer guides, and offer support to parents as moral educators.
Undergraduate Research